Peritoneal Dialysis Penetration and Peritonitis Rate at a Single Centre during Last Decade. (15th June 2011) - Uhlinova, Jana; Pechter, Ülle; Kermes, Kadri; Ots-Rosenberg, Mai
Abstract : Peritoneal dialysis (PD) has been intensively offered at our centre to patients (pts) with end-stage renal disease (ESRD) from 2000, and the number of PD pts was noticed to raise. We aimed to analyse the PD population from the aspect of penetration and peritonitis rate during eleven years. Cumulative number of new RRT pts was 378 during the study period. We found high PD penetration rate: 53% (range 32–72%). The rate of peritonitis was as high as 9.8 during first study years, but it has declined progressively last year being 29.1 by September 2010 and 21.7 by December 2010. Most cases of peritonitis were due to gram-positive pathogens. We have demonstrated steady high single-centre PD penetration rate and improvement of management of patients during last decade probably because of the result of better pts education and a continued dedication of the staff.